PENGARUH PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Merril) - Nahra Fahmi; Syamsuddin Syamsuddin; Ainun Marliah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
The research was aimed at determining effects of organic fertilizer D.I Grow and inorganic fertilizer NPK Yara Mila on growth and yield of soybean. The experiment was arranged in a completely randomized (CRD) 4 x 4 with 3 replications. There were two factors observed, that were 1) concentration of organic fertilizer D.I Grow, consisting of 4 levels : 0 mL/L of water, 1 mL/L of water, 3 mL/L of water and 5 mL/L of water, and 2) inorganic fertilizer NPK, consisting of 4 levels : 0 g/plant, 2,5 g/plant, 5,0 g/plant and 7,5 g/plant. Results showed that the concentration of fertilizer D.I Grow exerted highly significant effects on dry seed weight per plant, yield potential, and significant effects on plant height at 30 and 45 days after planting (DAP), stem diameter at 45 DAP, and seed dry weight of 100 grains, but did not exert significant effects on plant height at 15 DAP and stem diameter at 15 and 30 DAP. The best growth and yield were obtained at a concentration of DI Grow 5 mL /L of water. NPK fertilizer significantly affected plant height at 45 DAP, stem diameter at 30 and 45 DAP, dry seed weight per plant, and yield potential, but did not significantly affect plant height of 15 and 30 DAP, stem diameter at 15 DAP, weight of 100 grain and seed dry weight of 100 grains. The best growth and yield were obtained at a dose of 7.5 g NPK/plant. There were highly significant interactions between concentration of D.I Grow and dosage of NPK on dry seed weight per plant and yield potential. The best yield was obtained at a combination of D.I Grow 5 mL/L of water and 7.5 g of NPK plant .